2024
DOI: 10.1590/s1677-5538.ibju.2024.9909
|View full text |Cite
|
Sign up to set email alerts
|

Is the learning curve of the urology resident for conventional radical prostatectomy similar to that of staff initiating robot-assisted radical prostatectomy?

Rodrigo da Silva Pires,
Cláudio William Alves Pereira,
Luciano Alves Favorito

Abstract: Introduction:The superiority of the functional results of robot-assisted radical prostatectomyis still controversial. Despite this, it is known that minimally invasive surgery obtains better results when analyzing blood loss, blood transfusion and length of stay, for example.Several studies have analyzed the impact of the resident physician's involvement on the results of urological surgeries. The simple learning curve for robot-assisted radical prostate surgery is estimated to be around 10 to 12 cases. Learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Dr. Pires and collegues from Brazil performed in page 335 ( 7 ) a nice study about the learning curve of the urology resident for conventional radical prostatectomy (ORP) similar to that of staff initiating robot-assisted radical prostatectomy (RARP) and concluded that the learning curve of RARP is equivalent to the curve of ORP. In general, the results for the robotic group were better, however, the functional results were similar between the groups, with a slight tendency of advantage for the robotic arm.…”
mentioning
confidence: 99%
“…Dr. Pires and collegues from Brazil performed in page 335 ( 7 ) a nice study about the learning curve of the urology resident for conventional radical prostatectomy (ORP) similar to that of staff initiating robot-assisted radical prostatectomy (RARP) and concluded that the learning curve of RARP is equivalent to the curve of ORP. In general, the results for the robotic group were better, however, the functional results were similar between the groups, with a slight tendency of advantage for the robotic arm.…”
mentioning
confidence: 99%